Role of Acoustic Phonons in Forming Thermophysical Properties of PbI2 Nanofilms - Lutsiuk, Yu.V.; Kramar, V.M.; Konstantynovych, I.A. (Journal of Thermoelectricity, 2025)
Based on the dispersion dependences of acoustic phonon frequencies in hexagonal quasi-two-dimensional nanostructures, previously obtained by us in the elastic continuum approximation, the heat capacity, entropy, free energy (Helmholtz) and thermal diffusion coefficient of nanometer-thick planar structures (nanofilms) of lead diiodide were calculated. The dependence of these quantities on the thickness of the nanofilm and temperature, as well as the role of different branches of the phonon spectrum in the formation of the thermophysical properties of such structures, was studied. The results of the calculation of the heat capacity, entropy, free energy and thermal diffusion coefficient of lead diiodide nanofilms indicate that they all depend on the thickness of the nanofilm. This dependence is especially pronounced in ultrathin (up to 8 layered packages of PbI2) nanofilms. The absolute values ​​of all the indicated quantities increase with increasing temperature in nanofilms of any thickness. In the low temperature range, the rate of their growth is lower, the thinner the nanofilm. At temperatures above the Debye temperature, the growth of heat capacity and entropy slows down; the CV(T) dependence practically disappears, and the rate of growth of entropy S decreases the more strongly the greater the thickness of the nanofilm. Due to the difference in the rates of change of entropy in nanofilms of different thicknesses in the region T 400 K, the inversion of the S(T) dependence occurs - the entropy acquires values ​​that are greater, the thinner the nanofilm. The rate of change of the free energy value upon reaching the Debye temperature acquires its greatest value, so that with further increase in temperature, the free energy changes according to a linear law with a rate whose magnitude practically does not depend on the thickness of the nanofilm. It is shown that the greatest influence on thermophysical processes controlled by the values ​​of heat capacity, entropy and free energy is exerted by phonons of transverse polarizations - shear and bending. The phenomenon of thermal diffusion, like thermal conductivity, is determined mainly by longitudinal - dilational phonons.